Case reports of aesthetic rehabilitation by richmond crown in maxillary anterior teeth: A forgotten state of art - Neeta Patel; Athulya Pallipurath; Shwetika Patel; Gunja Malaviya; Sheena Patel; Mahek Zaveri (Wolters Kluwer Medknow Publications, 2023)
After endodontic therapy, restoring severely broken or damaged crown structure is a difficult task in conservative dentistry. Regular post and core followed by crown repair cannot restore a crown with steep incisal guidance, very little overjet, and highly damaged crown structure. Richmond crown is better recommended in these situations since Richmond crown is a crown having post. It is prepared as a single piece having a ceramic facing. We frequently encounter teeth having very less or no clinical crown portion that are structurally damaged. Support and retention of the restoration are challenging to achieve in such situations. The rehabilitation of anterior teeth that has been endodontically treated and structurally impaired is reviewed in two cases.